BALANCE BETWEEN LEADING AND FOLLOWING AND INTERNATIONAL PEDAGOGICAL INNOVATIONS - Radin, Michael; Orlova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The primary goal of this paper is to portray how the balance between leading and following can often guide us to new pedagogical innovations and leadership. First of all, we will examine how students’ feedback plays an essential role in devising new teaching styles that enhance the amiable learning atmosphere and directs us to new innovations and leadership. Second of all, we will focus on how feedback from colleagues can open new opportunities for new seminars, for new research projects, for writing new papers and textbooks and welcome us to new international and interdisciplinary teaching and learning atmosphere and new innovations. In addition, our aim is to address and understand the concerns and questions from students’ and colleagues’ feedback can be used to minimize the risk of failure and to steer us in designing new innovations and leadership. Furthermore, our intent is to portray that balance between leading and following is an essential technique in development of new ideas and innovations. Moreover, we will share examples of successful pedagogical innovations that were suggested by students and colleagues. Throughout this paper we will remit the following vital question: do creativity and innovations come directly from us?